The influence of Frayer model strategy towards students’ vocabulary mastery at the eighth class of SMPN 26 Bandar Lampung in 2017/2018 - Effrina Yuricki (Universitas Lampung, 2020)
Students’ vocabulary mastery is influenced by many factors. One of them is the technique, which the teachers use in teaching. In this research, the writer applied Frayer Model Strategy to teach vocabulary in the classroom. Then the writer analyzed the result of the technique in order to know its influence. The research was conducted at the eighth class of SMPN 26 Bandar Lampung in 2017/2018. The students of X1 were as the sample that was taught by using Frayer Model Strategy and X2 that was taught by using conventional technique. In this case, the writer used two classes as the sample, the first class as experimental class (29 students) and the second class as a control class (28 students) from 265 students of eight classes. The sample was gotten by random sampling technique and the research based on the experiment method. In collecting, the writer used objective test that was multiple-choice test contained 40 questions. The technique of analysis data in this research used product moment formulation. The result of the research shows that there is a significant influence of Frayer Model Strategy towards Students’ Vocabulary Mastery at the eighth class of SMPN 26 Bandar Lampung in 2017/2018. It showed from the distribution list with df = 55 obtained the t ratio t0.95 or significance level of 5% and t- ratio to 0.99 or significance level of 1% is equal to 2.02 and 2.70. They are less than t-test 7.16. Finally, the writer concluded that there is a significant influence of Frayer Model Strategy towards students’ vocabulary mastery at the eighth class of SMPN 26 Bandar Lampung in 2017/2018. dx.doi.org/10.23960/aksara/v21i2.pp145-155